On dynamic characteristics and stability analysis of the ducted fan unmanned aerial vehicles. (8th August 2019) - Chen, Cheng; Dong, Tiantian; Fu, Weijie; Liu, Na
This article researches the improvement of dynamics stability of the ducted fan unmanned aerial vehicles by optimizing its mechanical–structure parameters. The instability phenomenon of ducted fan unmanned aerial vehicles takes place frequently due to the complicated airflow in near-earth space, which easily leads to the stability problems, such as out of control, shaking, and loss accuracy of command tracking. The dynamics equations mirror its dynamics characteristics, which are primarily influenced by the mechanical–structure parameters of the whole system. Based on this, the optimization of mechanical–structure parameters has a significant to improve the dynamics stability of the whole system. Therefore, this article uses the concept of Lyapunov exponents to build the quantification relationship between system's mechanical–structure parameters and its motion stability to enhance its stability from viewpoint of mechanical–structural parameter design. The takeoff, landing, and hovering stage are respectively studied and the conclusions suggest that the optimization of mechanical–structure parameters can be used to promote dynamics stability.